PSYCHOSOCIAL AND BEHAVIORAL CORRELATES OF ANXIETY SYMPTOMS IN A SAMPLE OF HIV-POSITIVE, METHAMPHETAMINE-USING MEN WHO HAVE SEX WITH MEN - Semple, Shirley J. (2011)
Studies show high rates of psychiatric symptoms among methamphetamine users; however, little information exists regarding methamphetamine use and anxiety. This study investigated psychosocial and behavioral correlates of anxiety symptoms in a sample of 245 HIV-positive men having sex with men (MSM) who were enrolled in a sexual risk reduction intervention. In a multiple regression analysis, anxiety symptoms were associated with homelessness, recent experience of HIV symptoms, injection drug use, lifetime sexual abuse, engaging in risky sexual behaviors, and seeking out partners at risky sexual venues when “high” on methamphetamine. These findings can be used to inform and refine sexual risk reduction interventions and substance use treatment programs for HIV-positive methamphetamine-using MSM.